Caregivers of individuals with Rubinstein–Taybi syndrome: Perspectives, experiences, and relationships with medical professionals. Issue 1 (3rd July 2021) - Webster, Joshua; Wiley, Susan; Schorry, Elizabeth; Bowers, Katherine; Collins Ruff, Kathleen; Riddle, Ilka
Abstract: Rubinstein–Taybi syndrome (RTS) is a rare genetic disorder. Family‐centered care (FCC) is a healthcare delivery approach that aims to create an equal partnership between caregivers and providers. FCC has been shown to improve parental wellbeing, their knowledge of the condition and care, and improve their feelings of self‐efficacy and personal control. The purpose of this study was to explore the healthcare experiences of family caregivers of children and adults with RTS to understand the issues they encounter when working with medical professionals and to examine their perspectives on how to improve FCC. Primary family caregivers of individuals with RTS took an online mixed‐method survey that contained three primary components: a demographic survey, the Measures of Processes of Care‐20 (MPOC‐20) [a measure of the FCC an individual feels they receive], and a qualitative assessment of negative and positive interactions with medical professionals and priority areas for improvement. Qualitative data were analyzed using thematic analysis. Quantitative data were analyzed with descriptive statistics. An analysis of variance test was used to determine whether values statistically differed between different‐age groups of individuals with RTS being cared for. Sixty‐three caregivers completed the survey. The average score of the Providing General Information subscale of the MPOC‐20 was 3.18, lower than that seen in other studies. The average scores of the other subscales of the MPOC‐20 ranged from 4.60 to 5.02, comparable to other studies of caregivers of children with other medical conditions. All aspects of FCC were ranked as important by caregivers. There were no differences in MPOC‐20 values between those caring for the individuals with RTS in different‐age groups reviewed. In the qualitative responses, parents noted that experiences with medical professionals would be improved if healthcare providers actively provided FCC, collaborated with parents and other providers, respected caregivers' time and breadth of knowledge and lived experience, gave a more balanced description of the condition, showed greater respect toward their loved ones and included them in the conversation, and made an effort to learn about RTS. The changes that parents would like to see in their child's care were not specific to one discipline and could be implemented by all healthcare specialists. While caregivers report that they receive moderate levels of FCC, they indicated that areas of FCC could be improved.